Estrutura populacional e bioacumulação de metais em peixes de áreas afetadas por óleo no litoral brasileiro - Souza, Amanda da Silva (2023)
The entry of pollutants into aquatic ecosystems influences the population structure of fish and favors the bioaccumulation of chemical elements in organisms. In 2019, there was the largest oil spill off the coast of Brazil, and in this context, the aim of this study was to evaluate the population structure and bioaccumulation of metals in fish, Lutjanus synagris and Haemulon aurolineatum, from Itacaré (least affected area), Tinharé-Boipeba (most affected area) and Madre de Deus (chronically affected area). Total length, weight and condition factor were measured, and the sex, maturation stages and ontogenetic phase of the fish were identified. Metals were quantified in the muscle and liver using ICP-OES (Inductively Coupled Plasma). The lowest biometric values were recorded in the most critical areas in relation to the presence of oil, either the chronically affected area for H. aurolineatum or the area most affected by the accident on the coast for L. synagris. In both species, the body condition of the fish was higher in Itacaré (less affected by the oil). The results indicate that the oil disturbance may be influencing changes in the population aspects of the species. Metal contamination may have contributed to these differences. Some chemical elements negatively influenced growth (As, Ba and Cr), condition factor (As, Ba and Zn) and hepatosomatic index (HSI) (As, Ba, Cr, Zn and Fe), indicate that metal contamination may have reduced physiological indices. The liver was the main organ that bioaccumulated chemical elements. Most of the metals that differed showed higher levels in juvenile and immature fish. In muscle tissue, the concentration of As in ariacó was higher in Itacaré and in quatinga it was higher in Tinharé- Boipeba. In liver tissue, elemental levels were higher in fish from Madre de Deus, in both species. Only this population was contaminated by Pb, while the concentrations of As in the three areas were above or close to the maximum value acceptable to Anvisa. It is suggested that the oil spill may have impacted the species differently, also impacting fish from less affected areas. However, the concentrations of metals in the fish in Madre de Deus stood out when compared to the populations in the other areas studied. This study shows the influence of biological and environmental aspects on the bioaccumulation of metals in fish.